Atomistic simulations of poly(dimethyl siloxane) and poly(lactic acid) polymer systems for directed self assembly applications. - Κουλιεράκης, Ελευθέριος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Χημικών Μηχανικών, 2016)
Lithography has been the most important technology that has revolutionized the semiconductor and data storage industry. It is used in the fabrication of integrated circuits and microchips. However, conventional semiconductor lithography techniques become very expensive and inefficient when the feature size that has to be patterned is less than 30nm. In order to cross the Rubicon of scale miniaturization, alternative methods should be studied. One of the most promising potential candidates is the Directed Self Assembly of Block Copolymers. In order to guide the selection of the most suitable Block Copolymers for Directed Self Assembly applications, apart from experimental work, there is an urgent need for computational work as well. The Poly(dimethylsiloxane)-b-Poly(lactic acid) (PDMS-b-PLA) block copolymer is considered to be very suitable for directed self assembly applications due to its ability to self organize easily into tiny domains. A thermodynamic factor that describes the thermodynamic incompatibility between two different blocks in a block copolymer, and therefore controls the appearance of order from disorder is the Flory-Huggins interaction parameter q. PDMS-b-PLA appears to have a value of q significantly higher than that of other block copolymers, and thus, it will possibly enhance the Directed Self Assembly of Block Copolymers for Lithography purposes. In this work, a lot of attention is paid to estimating the χ parameter of PDMS-b-PLA. Apart from that, other volumetric, solubility and conformational properties of PDMS and PLA have been computationally studied by different simulation methods.